Topology-Based Modeling of Textile Structures and Their Joint Assemblies Principles, Algorithms and Limitations - Kyosev, Yordan (Springer International Publishing : Imprint: Springer, 2019)
This book presents the textile-, mathematical and mechanical background for the modelling of fiber based structures such as yarns, braided and knitted textiles. The hierarchical scales of these textiles and the structural elements at the different levels are analysed and the methods for their modelling are presented. The author reports about problems, methods and algorithms and possible solutions from his twenty year experience in the modelling and software development of CAD for textiles.